2023
DOI: 10.1186/s12939-022-01818-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the population affiliated to the subsidized health insurance scheme in Colombia: a systematic review and meta-analysis

Abstract: Background Some reports suggest there are differences in health needs between the population affiliated to the subsidized health insurance scheme (SS) and those affiliated to the contributory health insurance scheme (CS) in Colombia. The objective of this study was to identify the epidemiological profile of the population affiliated to the SS in Colombia and to compare the main epidemiological features of the SS to the CS. Methods Following the Pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Despite the country's social security system being based on the managed competition model, which led to increased coverage, some studies have found differences in the incidence, prevalence, and use of health services between the health affiliation schemes, and regional income inequality. 2 , 43 , 44 Another study found no education-based disparities in health-care experience despite high income inequality. 35 Putting these aspects in cross-national context, we found health system quality outcomes and levels of inequality largely similar to those in other study countries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the country's social security system being based on the managed competition model, which led to increased coverage, some studies have found differences in the incidence, prevalence, and use of health services between the health affiliation schemes, and regional income inequality. 2 , 43 , 44 Another study found no education-based disparities in health-care experience despite high income inequality. 35 Putting these aspects in cross-national context, we found health system quality outcomes and levels of inequality largely similar to those in other study countries.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several HPEs exhibit CPU loss ratios greater than 100%, with the maximum values being obtained in the SS. As the two schemes have populations with completely different risk profiles [ 33 ], there is an urgent need to use this information for an actuarial estimation of the CPU of the SS (to which more than 24 million people belong), since the Ministry of Health and Social Protection has generally made decisions regarding its growth based on whatever happens with the behavior of the CS, as was the case in 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, subsidiaries constitute a significant percentage, accounting for approximately 55% percent. Concurrently, 13% of the population is situated below the poverty datum line, highlighting prevalent economic challenges experienced by a substantial segment ( DANE, 2023 ; Mora-Moreo et al, 2023 ).…”
Section: About Colombiamentioning
confidence: 99%